The Influence of Job Crafting Training on Employee Work Engagement in General Elections Commission Purwakarta - Thesa Nur Adi Pratama; Missiliana Riasnugrahani; C.M. Indah Soca R. Kuntari (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2023)
The purpose of this study was to see the influence of job crafting training on employee work engagement in General Elections Commission districts Purwakarta before and after job crafting training. The sample in the study consisted twelve employees of General Elections Commission districts Purwakarta. The research used mixed methods research. The design used in this study is quasi-experimental (i.e., intervention group, N = 6, and a control group, N = 6). The research data were obtained from the UWES-17 (Utrecht Work Engagement Scale) [23]. The data processed with Wilcoxon and Mann-Whitney U statistic test. This study shows that job crafting training enhances work engagement in General Elections Commission district Purwakarta. This study suggests the agencies to provide job crafting training to all employees of General Elections Commission districts Purwakarta as an effort that can be to increase work engagement.